2022
DOI: 10.1093/jamia/ocac161
|View full text |Cite
|
Sign up to set email alerts
|

Utilization patterns and efficiency gains from use of a fully EHR-integrated COVID-19 self-triage and self-scheduling tool: a retrospective analysis

Abstract: Objective Symptom checkers can help address high demand for COVID-19 testing and care by providing patients with self-service access to triage recommendations. However, health systems may be hesitant to invest in these tools, as their associated efficiency gains have not been studied. We aimed to quantify the operational efficiency gains associated with use of an online COVID-19 symptom checker as an alternative to a telephone hotline. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…This result is consistent with findings from self-triage and self-scheduling of COVID PCR testing which showed savings of thousands of hours of nurse triage time and staff scheduler time. 5 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with findings from self-triage and self-scheduling of COVID PCR testing which showed savings of thousands of hours of nurse triage time and staff scheduler time. 5 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with findings from self-triage and self-scheduling of COVID PCR testing which showed savings of thousands of hours of nurse triage time and staff scheduler time. 5,12 It was out of the scope of this study to fully explore NVC that was associated with self-triage. However, our limited content review of over 400 patient-initiated messages showed that almost a third of them had content containing the terms "antibiotics" and "infection."…”
Section: Practice Implicationsmentioning
confidence: 99%
“… 10 Judson et al at University of California San Francisco also found significant time savings with self-scheduling of COVID visits. 9 Our findings show the potential to extend self-scheduling efficiencies well beyond COVID testing.…”
Section: Discussionmentioning
confidence: 73%
“…Patients are self-scheduling medical appointments with increasing regularity. Self-scheduling use cases have been published for community-based practices, 1 , 2 dermatology appointments, 3 , 4 screening mammograms, 5 , 6 well-child visits, 7 COVID testing, 8 10 and sexual health appointments. 11 Zocdoc and Lybrate are e-health services operating in the US and internationally that schedule patients online with providers by focus on their practice, specialty, and location.…”
Section: Introductionmentioning
confidence: 99%
“…To help reduce ED visits and make COVID care and detection more efficient, Mayo Clinic and the University of California, San Francisco successfully developed online self-triage and self-scheduling systems for COVID that diverted asymptomatic and symptomatic patients without severe symptoms to outpatient testing, thus avoiding ED visits. [10][11][12] These interventions for COVID demonstrated the potential for broader interventions to decrease unnecessary ED visits.…”
Section: Introductionmentioning
confidence: 99%